Hydrothermal synthesis of ZnO nanostructures with controllable morphology change. Issue 8 (3rd February 2020) - Gerbreders, Vjaceslavs; Krasovska, Marina; Sledevskis, Eriks; Gerbreders, Andrejs; Mihailova, Irena; Tamanis, Edmunds; Ogurcovs, Andrejs
Abstract : Optimal synthesis parameters for hydrothermal growth of nine ZnO nanostructure morphologies as a durable, homogeneous coating have been determined. Abstract : Amongst the most popular methods for the production of metal oxide nanostructures is hydrothermal synthesis. For producing ZnO nanostructures, a nitrate-based precursor reaction with equimolar amounts of hexamethylenetetramine (HMTA) is commonly used. In these reactions, zinc nitrate provides the source of Zn 2+ ions, and HMTA produces the desired amount of OH − ions. The growth process occurs due to a dissolution-secondary precipitation mechanism. ZnO nanostructures are characterized by anisotropic growth with different growth rates of the individual faces, where ( v (0001) > v (101̄0) > v (101̄1̄) > v (101̄1) > v (0001̄)). Therefore, considering the principle of energy minimization, the most favorable is vertical growth perpendicular to the (0001) plane, which ensures the formation of characteristic rod-like nanostruchtures of ZnO. The mentioned process takes place when chemical reactions are in equilibrium. Shifting from the equilibrium conditions by varying the parameters of reaction, or using capping agents, makes it possible to change the growth rate of individual crystallographic planes and, as result, affect the morphology of the obtained nanostructure. In this paper the influence of concentration and composition of the reagents, growth time and temperature, pH of the solution, and the presence of different capping agents on the growth process of nanostructured ZnO were investigated. Optimal synthesis parameters for obtaining nine independent ZnO morphologies have been determined. The distinctive feature of these experiments is the fact that the samples were obtained as durable, homogeneous, epitaxial coatings on hard surfaces. This can be especially interesting for the development of sensors and other fields where surface area is crucial, and it opens up more possibilities than use of the nanostructured ZnO powders.